Preparation method of in-situ esterified nanocellulose fibrils based on plant straws

Through the pretreatment of biological compound enzyme preparation of plant straw, deep eutectic solvent dissociation-in-situ esterification reaction and oxidation treatment, combined with mechanical treatment, the problems of large amount of chemical reagents and high energy consumption in nanocellulose preparation are solved, and the problem of high energy consumption is achieved. High-efficiency and low-cost nanocellulose filament preparation, high-purity and stability products were obtained, and large-scale production of nanocellulose was promoted.

CN119265977APending Publication Date: 2025-01-07DALIAN POLYTECHNIC UNIVERSITY +1

Patent Information

Application Number
CN202411619034.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

During the preparation of nanocellulose, there are problems such as large amount of chemical reagents, difficulty in recycling, high energy consumption, and consumption of a large amount of energy during mechanical treatment, resulting in environmental pollution and low production efficiency, hindering its large-scale production and widespread production. application.

Method used

Using the preparation method of in situ esterified nanocellulose filaments based on plant straw, the multi-step process of biological compound enzyme preparation pretreatment, deep eutectic solvent dissociation-in situ esterification reaction, oxidation treatment and mechanical treatment is realized. Highly efficient, low-cost and environmentally friendly nanocellulose filament preparation.

Benefits of technology

In-situ esterified nanocellulose filaments with high purity, uniform size and high stability were obtained, which reduced energy consumption, avoided solvent waste and environmental pollution, and supported the large-scale production of nanocellulose and the bio-based materials industry. develop.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265977A_ABST
    Figure CN119265977A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of in-situ esterified nano cellulose fibrils based on plant straws. Comprising the following steps: mixing deionized water, plant straw powder and a biological compound enzyme preparation, and carrying out enzymatic reaction on the mixed solution to obtain enzyme-pretreated plant straw powder; mixing a deep eutectic solvent with the enzyme-pretreated plant straw powder, and carrying out a dissociation-in-situ esterification reaction on the mixed solution to obtain in-situ esterified holocellulose; mixing deionized water, in-situ esterified holocellulose and an oxidizing agent, carrying out oxidation reaction on the mixed solution, and carrying out suction filtration on the reaction solution to obtain in-situ esterified cellulose; and carrying out mechanical treatment on the aqueous dispersion of the in-situ esterified cellulose to obtain the in-situ esterified nanocellulose fibrils. According to the present invention, the multi-dimensional co-treatment preparation technology integrating biological pretreatment, in-situ chemical modification and mechanical dissociation is adopted, such that the in-situ esterified cellulose fibril can be rapidly, efficiently and environmentally-friendly prepared, the prepared nano cellulose fibril has characteristics of high purity, uniform size and high stability, and the large-scale production can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of nanomaterials, and in particular to a method for preparing in-situ esterified nanocellulose fibrils based on plant straw. Background Art

[0002] Cellulose is the most abundant sustainable biological resource on earth and is gradually becoming an important substitute for petroleum-based products. Cellulose is widely distributed in plants such as trees, herbs, algae, and crops, and constitutes the main structure of plant cell walls.

[0003] Nanocellulose is a fiber-based nanomaterial obtained from natural plants through pretreatment, purification, mechanical treatment and other processes, with a diameter of no more than 50nm and a length of at least 500nm. Nanocellulose fibrils have the characteristics of high strength, high modulus, high specific surface area, biodegradability, and renewability, and they show great potential in the fields of new material development, renewable energy production, and environmentally friendly product manufacturing.

[0004] Although nanocellulose is a biomass material with great potential, its preparation process still faces many technical challenges and limitations. The first problem is that the chemical treatment method requires a large amount of chemical reagents and is difficult to recycle. If not handled properly, it may cause environmental pollution. The second problem is that the mechanical treatment process consumes a lot of energy to destroy the hydrogen bonds between cellulose molecules. In addition, the large-scale production and widespread application of nanocellulose still face multiple challenges.

[0005] Therefore, it is urgent to develop a method for preparing nanocellulose fibrils with high efficiency, low cost and environmentally friendly properties to promote large-scale production in the nanocellulose industry and promote the development of the bio-based materials industry. Summary of the invention

[0006] In view of the shortcomings in the preparation and application of the above-mentioned nanocellulose fibrils, the purpose of the present application is to provide a method for preparing nanocellulose fibrils by in-situ esterification based on plant straw. The preparation method is efficient, low-cost and environmentally friendly, and the prepared nanocellulose fibrils have the characteristics of high purity, high aspect ratio, uniform size and high stability.

[0007] The purpose of this application is achieved through the following technical solutions.

[0008] In a first aspect of the present application, a method for preparing in-situ esterified nanocellulose fibrils based on plant straw is provided, comprising the following steps:

[0009] (1) washing, drying, and crushing plant straw to obtain plant straw powder;

[0010] (2) mixing deionized water, plant straw powder and a biological composite enzyme preparation, and subjecting the mixed solution to an enzymatic reaction to obtain enzyme-pretreated plant straw powder;

[0011] (3) mixing the deep eutectic solvent and the enzyme pretreated plant straw powder, and subjecting the mixed solution to a dissociation-in situ esterification reaction to obtain in situ esterified holocellulose;

[0012] (4) mixing deionized water, the in-situ esterified holocellulose and an oxidant, subjecting the mixed solution to an oxidation reaction, and filtering the reaction solution to obtain the in-situ esterified cellulose;

[0013] (5) adding water to the in-situ esterified cellulose to obtain a dispersion, and subjecting the dispersion to mechanical treatment to obtain in-situ esterified nanocellulose fibrils.

[0014] In any embodiment of the present application, in step (1), the plant straw is preferably one or more of wheat straw, corn straw, rice straw, soybean straw, sorghum straw, cotton straw, hemp straw, rape straw, and sweet potato straw, but the plant straw used in the present application is not limited to these plant straws, and plant straw from other plant sources may also be used.

[0015] In any embodiment of the present application, in step (1), during the cleaning process, deionized water is used as a cleaning liquid to clean the plant straw as a raw material 1 to 3 times to remove impurities such as dust.

[0016] In any embodiment of the present application, in step (1), in the drying step, the drying temperature is 60 to 120° C., preferably 80 to 120° C. Generally, the drying is performed until the moisture content is below 10%.

[0017] In any embodiment of the present application, in step (1), in the pulverizing step, the dried plant straw is pulverized by a pulverizer or the like, and the pulverized particle size is 30 to 300 meshes, preferably 50 to 300 meshes.

[0018] In any embodiment of the present application, in step (2), the biological compound enzyme preparation is one or more of pectinase, cellulase, hemicellulase, laccase, and amylase, and the mass ratio of the pectinase, cellulase, hemicellulase, laccase, and amylase is (1-10): (1-10): (1-10): (1-8): (1-8), preferably (2-10): (2-10): (2-10): (2-6): (2-6). Preferably, the biological compound enzyme preparation is a mixture of pectinase and cellulase, and more preferably, the biological compound enzyme preparation is a mixed enzyme composed of pectinase, cellulase, hemicellulase, laccase, and amylase.

[0019] In step (2) of the present application, a biological composite enzyme preparation composed of specific enzymes is used to pre-treat the dried plant straw, thereby effectively destroying the coating of lignin and hemicellulose on cellulose, exposing cellulose, so that it is easy to be esterified in the next reaction. Specifically, the biological composite enzyme preparation used in the present application contains pectinase, which is conducive to the degradation of pectin and promotes the softening of plant tissues; contains cellulase, which is conducive to shortening the length of cellulose fibrils and reducing the energy consumption of subsequent processes; contains hemicellulase and laccase at the same time, which can effectively act on the degradation process of hemicellulose and lignin, can effectively destroy the coating of lignin and hemicellulose on cellulose, contains amylase, hydrolyzes the starch and glycogen contained in the plant straw, and reduces the energy consumption of subsequent processes such as filtration. For the pectinase, cellulase, hemicellulase, laccase, and amylase used, the corresponding enzymes prepared by conventional methods in the art or commercially available can be used, preferably the corresponding enzymes prepared by conventional methods in the art suitable for enzyme treatment of plant straw or commercially available. In one embodiment, the pectinase is derived from Aspergillus niger, and a commercially available pectinase preparation generated by a selected strain of Aspergillus niger can be used. Preferably, the pectinase is a mixture of one or two of pectin lyase, pectin esterase and pectin hydrolase, or a mixture of three, preferably a mixture of three; the cellulase is a mixture of one or two of endoglucanase, exoglucanase and β-glucosidase, or a mixture of three, preferably a mixture of three; the hemicellulase is a mixture of one or two of xylanase, mannanase, arabinofuranosidase and acetylxylan esterase, or a mixture of three or four, preferably a mixture of three or four; the amylase is a mixture of one or two of α-amylase, β-amylase and glucoamylase, or a mixture of three, and the laccase is derived from Aspergillus. In the case of multiple (two, three, four) mixed enzymes, the content relationship of each component is not particularly limited, and the corresponding enzymes obtained by conventional methods in the art or commercially available can be used.

[0020] In any embodiment of the present application, in step (2), the solid-liquid mass ratio of the deionized water, plant straw powder and biological composite enzyme preparation is 200:(5-40):(1-10), preferably 200:(10-30):(2-8).

[0021] In any embodiment of the present application, in step (2), phosphate buffer dry powder and ethylenediaminetetraacetic acid (EDTA) dry powder are added to the mixed solution in a solid-liquid mass ratio of (1 to 6): (1 to 6).

[0022] In any embodiment of the present application, in step (2), the pH value of the mixed solution is adjusted to 7 to 11, preferably 8 to 10. Preferably, sodium hydroxide is used to adjust the pH value of the mixed solution.

[0023] In any embodiment of the present application, in step (2), the reaction temperature of the enzymatic reaction is 30°C to 90°C, preferably 40°C to 80°C.

[0024] In any embodiment of the present application, in step (2), the reaction time of the enzymatic reaction is 0.5h to 6h, preferably 1h to 6h. In a specific embodiment, the enzymatic reaction time can be determined according to the reducing sugar content determination, etc., and the reaction is terminated when the raw sugar content no longer increases significantly.

[0025] In any embodiment of the present application, in step (2), after the enzymatic reaction is completed, the reaction solution is filtered at room temperature, solid-liquid separation is performed using a vacuum filtration device, and the filter cake is repeatedly washed with deionized water until the pH value of the filtrate reaches 7 to 8; the washed solid is dried at 70 to 90° C. for 4 to 8 hours until the moisture content of the material drops below 10%, thereby obtaining enzyme-pretreated plant straw powder.

[0026] In any embodiment of the present application, in step (3), the deep eutectic solvent comprises a hydrogen bond acceptor and a hydrogen bond donor, the hydrogen bond acceptor is one or more of betaine, choline chloride, choline carbonate, and 1-butyl-3-methylimidazolium chloride, and the hydrogen bond donor is one or more of formic acid, acetic acid, lactic acid, oxalic acid, acrylic acid, and citric acid, and the solid-liquid mass ratio of the hydrogen bond acceptor to the hydrogen bond donor in the deep eutectic solvent is 5:(1-30), preferably 5:(1-25).

[0027] In any embodiment of the present application, in step (3), the solid-liquid mass ratio of the deep eutectic solvent to the enzyme-pretreated plant straw powder is 100:(1-30), preferably 100:(1-20).

[0028] In any embodiment of the present application, in step (3), the reaction temperature of the dissociation-in situ esterification reaction is 40°C to 170°C, preferably 50 to 150°C.

[0029] In any embodiment of the present application, in step (3), the reaction time of the dissociation-in situ esterification reaction is 0.5 to 6 hours, preferably 1 to 5 hours.

[0030] In any embodiment of the present application, in step (3), after the dissociation-in situ esterification reaction is completed, ethanol or acetone is added to the reaction solution, filtered to obtain in situ esterified holocellulose solid and filtrate I, the solvent (i.e., ethanol or acetone) in filtrate I is separated by rotary distillation or the like, water is added to the remaining filtrate, stirred, filtered and washed to obtain lignin solid and filtrate II, and after separating the water in filtrate II, a reusable deep eutectic solvent is obtained.

[0031] In step (3) of the present application, a deep eutectic solvent is mixed with enzyme-pretreated plant straw powder for reaction. During the reaction, the deep eutectic solvent selectively dissolves part of the lignin and hemicellulose by destroying the hydrogen bond network of cellulose-lignin-hemicellulose, and performs an in-situ esterification reaction on the cellulose. After the reaction is completed, the reaction solution is diluted by adding an appropriate amount of ethanol or acetone to separate the deep eutectic solution in the reaction solution from the in-situ esterified holocellulose solid. The diluted reaction solution is filtered to obtain two main products: a mixed solution of deep eutectic solvent and lignin (filtrate I) and an in-situ esterified holocellulose solid. After the deep eutectic solvent and lignin mixed solution (filtrate I) are rotary evaporated to separate ethanol or acetone, deionized water is added for washing and filtration to obtain lignin solids and a mixed solution of deep eutectic solvent and water (filtrate II). The deep eutectic solvent and water mixed solution (filtrate II) are rotary evaporated to separate water to obtain a reusable deep eutectic solvent. The lignin solid obtained in this step has a high purity and can be directly used as an industrial raw material for the preparation of products containing lignocellulose.

[0032] In any embodiment of the present application, in step (4), the oxidant is one or more of ozone, potassium permanganate, hydrogen peroxide, sodium persulfate, ammonium persulfate, sodium chlorite, and sodium hypochlorite.

[0033] In any embodiment of the present application, in step (4), the solid-liquid mass ratio of the deionized water, the in-situ esterified holocellulose, and the oxidant is 100:(3-30):(1-15), preferably 100:(5-20):(1-10).

[0034] In any embodiment of the present application, in step (4), the pH value of the mixed solution is 2-12, preferably 3-11.

[0035] In any embodiment of the present application, in step (4), the reaction temperature of the oxidation reaction is 30°C to 90°C, preferably 40°C to 80°C.

[0036] In any embodiment of the present application, in step (4), the reaction time of the oxidation reaction is 0.5 h to 6 h, preferably 1 h to 5 h.

[0037] In step (4) of the present application, a specific oxidant is used to react with the in-situ esterified holocellulose. During the reaction, the oxidant breaks down the molecular chains of lignin and hemicellulose, decomposing the two into smaller fragments, thereby separating them from the in-situ esterified cellulose. After the reaction is completed, solid-liquid separation is performed by filtering and washing to obtain in-situ esterified cellulose solids.

[0038] In any embodiment of the present application, in step (5), the solid-liquid mass ratio of deionized water and the in-situ esterified holocellulose in the dispersion is 100:(0.1-30), preferably 100:(0.2-20).

[0039] In any embodiment of the present application, in step (5), the mechanical treatment is ultrasonic treatment, the ultrasonic frequency of the ultrasonic treatment is 5-100 kHz, the power range is 50-700 W, and the treatment time is 1-90 min. Preferably, the frequency of the ultrasonic treatment is 10-80 kHz, the power range is 100-600 W, and the treatment time is 5-60 min.

[0040] In any embodiment of the present application, in step (5), the mechanical treatment is ball milling, the rotation speed of the ball milling is 50-1100 rpm / min, and the treatment time is 1-90 min. Preferably, the rotation speed of the ball milling is 100-1000 rpm / min, and the treatment time is 5-60 min.

[0041] In any embodiment of the present application, in step (5), the mechanical treatment is a high-speed dispersion treatment, the rotation speed of the high-speed dispersion treatment is 1000-100000 rpm / min, and the treatment time is 1-90 min. Preferably, the rotation speed of the high-speed dispersion treatment is 1000-9000 rpm / min, and the treatment time is 5-60 min.

[0042] In any embodiment of the present application, in step (5), the mechanical treatment is a high-pressure homogenization treatment, the treatment pressure of the high-pressure homogenization treatment is 500-3000 bar, the treatment flow rate is 10-2000 mL / h, and the treatment time is 1-90 min. Preferably, the treatment pressure of the high-pressure homogenization treatment is 500-2000 bar, the treatment flow rate is 15-1000 mL / h, and the treatment time is 5-60 min.

[0043] Beneficial effects of this application:

[0044] First, the biocomposite enzyme preparation composed of specific enzymes can effectively destroy the coating of lignin and hemicellulose on cellulose, which helps to improve the efficiency of the subsequent steps. This step utilizes the high selectivity and mild conditions of the enzymatic reaction to avoid the high pollution and high energy consumption problems common in traditional chemical methods.

[0045] Secondly, deep eutectic solvent treatment can dissociate cellulose from the coating of lignin and hemicellulose. During the dissociation process of cellulose, the organic acid in the deep eutectic solvent reacts with the hydroxyl groups on the cellulose molecules in situ to form in situ esterified holocellulose microfibrils. Deep eutectic solvent has a good ability to dissolve lignin and hemicellulose and is recyclable, which ensures that cellulose is efficiently dissociated and in situ esterified while avoiding solvent waste and environmental impact.

[0046] After deep eutectic solvent treatment, oxidation treatment can reduce the content of lignin and hemicellulose. While improving the purity of raw cellulose, reducing the energy consumption of cellulose nanocrystallization process optimizes the overall efficiency.

[0047] Finally, appropriate mechanical treatment can further improve the nano-sizing degree of in situ esterified cellulose, and ultimately obtain in situ esterified nanocellulose fibrils; while ensuring the nano-sizing of in situ esterified cellulose, mechanical treatment maintains the aspect ratio and dispersity of the in situ esterified fibers, thereby improving the application performance of the in situ esterified nanocellulose fibrils.

[0048] The preparation method of the present application includes the steps of biological compound enzyme preparation treatment, deep eutectic solvent treatment, oxidant treatment, and mechanical treatment in sequence. On the one hand, by integrating the multi-dimensional synergistic treatment preparation technology of biological pretreatment, in-situ chemical modification and mechanical dissociation, in-situ esterified cellulose fibrils can be prepared quickly, efficiently and greenly. On the other hand, lignin solids as by-products can be prepared in the deep eutectic solvent treatment step, which have high purity and can be directly used as industrial raw materials. The purity of the nanocellulose fibrils prepared according to the method of the present application is as high as 95% or more, the fibril diameter is less than 5nm, the length is more than 500nm, and it has a high aspect ratio. The size of the prepared fibrils is uniform and the stability is high, which can realize large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is the FTIR image of corn stover and in-situ esterified nanocellulose fibrils in Example 1.

[0050] Figure 2 This is the FTIR image of hemp straw and in-situ esterified nanocellulose fibrils in Example 2.

[0051] Figure 3 This is the XRD pattern of corn stover and in-situ esterified nanocellulose fibrils in Example 1.

[0052] Figure 4 This is the XRD diagram of hemp straw and in-situ esterified nanocellulose fibrils in Example 2.

[0053] Figure 5 This is the TEM image of the in situ esterified nanocellulose fibrils prepared from corn straw in Example 1.

[0054] Figure 6 This is the TEM image of the in situ esterified nanocellulose fibrils prepared from hemp straw in Example 2. DETAILED DESCRIPTION

[0055] In order to make the technical solution of the present application clearer, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. The specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0056] In the following examples, unless otherwise specified, the experimental methods used are all conventional methods, and the reagents used can be purchased from chemical or biological reagent companies.

[0057] Materials used in the following examples:

[0058] Pectinase: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product model: P116864.

[0059] Cellulase: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product model: C109262.

[0060] Hemicellulase: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product model: H822630.

[0061] Amylase: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product model: D799254.

[0062] Laccase: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product model: L753822.

[0063] Example 1

[0064] 1. Preparation of plant straw powder: First, cut the corn straw into a suitable length, soak it in deionized water for 1 hour and rinse it for 5 minutes, and repeat the soaking and rinsing process twice; place the washed corn straw in a constant temperature forced air drying oven at 80°C for drying until its quality is stable and no longer changes; finally, the dried corn straw is crushed using an ultra-fine mechanical crusher, and the crushed corn straw is sieved with a 100-mesh screen to remove larger particles to obtain corn straw powder.

[0065] 2. Pretreatment of biological compound enzyme preparation: first mix deionized water, corn straw powder, pectinase, cellulase, hemicellulase, laccase, amylase, phosphate buffer dry powder and ethylenediaminetetraacetic acid in the proportions of 1000mL, 200g, 10g, 5g, 10g, 5g, 5g, 4g, 4g; adjust the pH value of the mixture to 9; then stir the mixture at 70°C for 3h; then filter the mixture, wash it to neutrality and dry it to obtain enzyme-pretreated corn straw powder.

[0066] 3. Deep eutectic solvent treatment: first, the hydrogen bond acceptor (choline chloride) and hydrogen bond donor (oxalic acid) of the deep eutectic solvent are mixed in a solid-liquid mass ratio of 1:4, and dissolved at 90°C for later use; the deep eutectic solvent and the enzyme pretreated plant straw powder are mixed in a ratio of 1000g and 100g; then the mixture is stirred at 130°C for 4h; after the stirring is completed, ethanol is added for suction filtration and washing to obtain the in-situ esterified holocellulose solid and the mixed solution of the deep eutectic solvent and lignin;

[0067] After the ethanol is separated from the mixed solution of deep eutectic solvent and lignin by rotary evaporation, deionized water is added for filtration and washing to obtain lignin solid and a mixed solution of deep eutectic solvent and water. After the water is separated from the mixed solution of deep eutectic solvent and water by rotary evaporation, a reusable deep eutectic solvent is obtained.

[0068] 4. Oxidant treatment: first, deionized water, the in situ esterified holocellulose solid obtained in step 3, and hydrogen peroxide (30%) were mixed in a ratio of 1000 mL, 80 g, and 20 mL; the pH value of the mixture was adjusted to 4; the mixture was stirred at 60°C for 3 h; after the stirring was completed, deionized water was added for suction filtration and washing to obtain an in situ esterified cellulose solid with a solid content of 15%.

[0069] 5. Mechanical treatment: first, deionized water and the in-situ esterified cellulose solid obtained in step 4 were mixed in a ratio of 650 mL and 100 g; ultrasonic treatment was performed using an ultrasonic disperser, the ultrasonic treatment frequency was adjusted to 40 kHz, the power range was 500 W, the treatment time was 30 min, and an in-situ esterified nanocellulose fibril dispersion with a concentration of 2% was obtained after ultrasonic treatment.

[0070] Example 2

[0071] 1. Preparation of plant straw powder: first cut the hemp straw into a suitable length, soak it in deionized water for 2 hours and rinse it for 10 minutes, and repeat the soaking and rinsing process once; place the washed hemp straw in a constant temperature blast drying oven at 85°C for drying until its quality is stable and no longer changes; finally, the dried hemp straw is crushed using an ultra-fine mechanical crusher, and the crushed hemp straw is sieved with a 120-mesh screen to remove larger particles to obtain hemp straw powder.

[0072] 2. Pretreatment with biological compound enzyme preparation: first mix deionized water, hemp straw powder, pectinase, cellulase, hemicellulase, laccase, amylase, phosphate buffer powder and ethylenediaminetetraacetic acid in the proportions of 1000 mL, 300 g, 8 g, 6 g, 8 g, 6 g, 6 g, 3 g, and 3 g; adjust the pH value of the mixture to 10; then stir the mixture at 60 ° C for 2 h; then filter the mixture, wash it to neutrality and dry it to obtain enzyme-pretreated hemp straw powder.

[0073] 3. Deep eutectic solvent treatment: first, the hydrogen bond acceptor (betaine) and hydrogen bond donor (citric acid) of the deep eutectic solvent are mixed in a solid-liquid mass ratio of 1:2, and dissolved at 90°C for later use; the deep eutectic solvent and the enzyme pretreated plant straw powder are mixed in a ratio of 1000g and 120g; then the mixture is stirred at 120°C for 3h; after the stirring is completed, ethanol is added for suction filtration and washing to obtain the in-situ esterified holocellulose solid and the mixed solution of the deep eutectic solvent and lignin;

[0074] After the ethanol is separated from the mixed solution of deep eutectic solvent and lignin by rotary evaporation, deionized water is added for extraction and washing to obtain lignin solid and a mixed solution of deep eutectic solvent and water. After the water is separated from the mixed solution of deep eutectic solvent and water by rotary evaporation, a reusable deep eutectic solvent is obtained.

[0075] 4. Oxidant treatment: first, deionized water, the in situ esterified holocellulose solid obtained in step 3, and sodium hypochlorite (3%) were mixed in a ratio of 1000 mL, 100 g, and 50 mL; the pH value of the mixture was adjusted to 7; the mixture was stirred at 60° C. for 3 h; after the stirring, deionized water was added for suction filtration and washing to obtain an in situ esterified cellulose solid with a water content of 13%.

[0076] 5. Mechanical treatment: Deionized water and the in-situ esterified cellulose solid obtained in step 4 were mixed in a ratio of 550 mL and 100 g, and then ball milled using a ball mill at a speed of 800 rpm / min for 30 min. After ball milling, an in-situ esterified nanocellulose fibril dispersion with a concentration of 2% (m / v) was obtained.

[0077] Example 3

[0078] Figure 1 to Figure 6 The results of physical and chemical property tests of in-situ esterified nanocellulose fibrils obtained according to Example 1 and Example 2 are shown in FIG.

[0079] Figure 1 FTIR images of corn stalks and in-situ esterified nanocellulose fibrils in Example 1. Figure 1The changes in the absorption peak positions show that the 1594 and 1508 cm -1 The C=C stretching vibration of the aromatic ring and 1464 and 835 cm -1 The CH bending vibration of the aromatic ring disappeared, proving the removal of lignin. -1 The C=O stretching vibration peak in hemicellulose disappears, and the peak at 1736 cm -1 The C=O stretching vibration peak of cellulose esterification appears at .

[0080] Figure 2 This is the FTIR image of hemp straw and in-situ esterified nanocellulose fibrils in Example 2. Figure 2 The changes in the absorption peak positions show that the 1597 and 1507 cm -1 The C=C stretching vibration of the aromatic ring and 1464 and 835 cm -1 The CH bending vibration of the aromatic ring disappeared, proving the removal of lignin. -1 The C=O stretching vibration peak in hemicellulose disappears, and the peak at 1735 cm -1 The C=O stretching vibration peak of cellulose esterification appears at .

[0081] Figure 3 The XRD diagram of corn stalks and in-situ esterified nanocellulose fibrils in Example 1. Figure 3 The XRD diffraction pattern shows that the crystallinity of corn stalks is 62.3%, and the crystallinity of in-situ esterified nanocellulose fibrils prepared from corn stalks is 68.1%. This indicates that after the corn stalks are pretreated with a biocomposite enzyme preparation, treated with a deep eutectic solvent, and treated with an oxidant, components such as pectin, lignin, and hemicellulose are effectively removed, and the obtained in-situ esterified nanocellulose fibrils have a high crystallinity, indicating that the present application can effectively improve the purity of in-situ esterified nanocellulose fibrils.

[0082] Figure 4 The XRD diagram of hemp straw and in-situ esterified nanocellulose fibrils in Example 2. Figure 4 The XRD diffraction pattern shows that the crystallinity of hemp straw is 64.5%, and the crystallinity of in-situ esterified nanocellulose fibrils is 75.4%. This indicates that after the hemp straw is pretreated with a biological compound enzyme preparation, treated with a deep eutectic solvent, and treated with an oxidant, components such as pectin, lignin, and hemicellulose are effectively removed, and the obtained in-situ esterified nanocellulose fibrils have a high crystallinity, indicating that the present application can effectively improve the purity of in-situ esterified nanocellulose fibrils.

[0083] Figure 5 TEM image of in situ esterified nanocellulose fibrils prepared from corn stalks in Example 1. Figure 5 It can be seen that by analyzing the size of the in situ esterified nanocellulose fibrils, it was found that the in situ esterified nanocellulose fibrils were well dispersed without agglomeration, and the diameter of the in situ esterified nanocellulose fibrils was below 6 nm and the length was above 500 nm.

[0084] Figure 6 TEM image of in-situ esterified nanocellulose fibrils prepared from hemp straw in Example 2. Figure 6 It can be seen that by analyzing the size of the in situ esterified nanocellulose fibrils, it was found that the in situ esterified nanocellulose fibrils were well dispersed without agglomeration, and the diameter of the in situ esterified nanocellulose fibrils was below 5 nm and the length was above 500 nm.

Claims

1. A method for preparing in-situ esterified nanocellulose fibrils based on plant straw, characterized in that: The steps include: (1) washing, drying, and crushing plant straw to obtain plant straw powder; (2) mixing deionized water, plant straw powder and a biological composite enzyme preparation, and subjecting the mixed solution to an enzymatic reaction to obtain an enzyme-pretreated plant straw powder; (3) mixing the deep eutectic solvent and the enzyme pretreated plant straw powder, and subjecting the mixed solution to a dissociation-in situ esterification reaction to obtain in situ esterified holocellulose; (4) mixing deionized water, the in-situ esterified holocellulose and an oxidant, subjecting the mixed solution to an oxidation reaction, and filtering the reaction solution to obtain the in-situ esterified cellulose; (5) adding water to the in-situ esterified cellulose to obtain a dispersion, and subjecting the dispersion to mechanical treatment to obtain in-situ esterified nanocellulose fibrils.

2. The preparation method according to claim 1, characterized in that: In step (1), The plant straw is one or more of wheat straw, corn straw, rice straw, soybean straw, sorghum straw, cotton straw, hemp straw, rape straw, and sweet potato straw; and / or, During the cleaning, deionized water is used as a cleaning liquid for 1 to 3 times; and / or, The drying temperature of the drying is 60-120° C.; and / or, In the pulverizing, the plant straw has a pulverized particle size of 30 to 300 meshes.

3. The preparation method according to claim 1, characterized in that: In step (2), the biological composite enzyme preparation is one or more of pectinase, cellulase, hemicellulase, laccase, and amylase, and the mass ratio of the pectinase, cellulase, hemicellulase, laccase, and amylase is (1-10): (1-10): (1-10): (1-8): (1-8).

4. The preparation method according to claim 2, characterized in that: The pectinase is one or more of pectin lyase, pectin esterase, and pectin hydrolase; the cellulase is one or more of endoglucanase, exoglucanase, and β-glucosidase; the hemicellulase is one or more of xylanase, mannanase, arabinofuranosidase, and acetylxylan esterase; the amylase is one or more of α-amylase, β-amylase, and glucoamylase; and the laccase is derived from Aspergillus.

5. The preparation method according to claim 1, characterized in that: In step (2), The solid-liquid mass ratio of the deionized water, the plant straw powder and the biological compound enzyme preparation is 200:(5-40):(1-10); and / or, Phosphate buffer solution powder and ethylenediaminetetraacetic acid powder are added to the mixed solution in a solid-liquid mass ratio of (1-6): (1-6); and / or, Adjusting the pH value of the mixed solution to 7-11; and / or, The reaction temperature of the enzymatic reaction is 30°C to 90°C; and / or, The reaction time of the enzymatic reaction is 0.5 to 6 hours; and / or, After the enzymatic reaction is completed, the reaction solution is filtered, washed and dried to obtain the enzyme pretreated plant straw powder.

6. The preparation method according to claim 1, characterized in that: In step (3), the deep eutectic solvent includes a hydrogen bond acceptor and a hydrogen bond donor, the hydrogen bond acceptor is one or more of betaine, choline chloride, choline carbonate, and 1-butyl-3-methylimidazolium chloride, and the hydrogen bond donor is one or more of formic acid, acetic acid, lactic acid, oxalic acid, acrylic acid, and citric acid, and the solid-liquid mass ratio of the hydrogen bond acceptor to the hydrogen bond donor in the deep eutectic solvent is 5:(1-30).

7. The preparation method according to claim 1, characterized in that: In step (3), The solid-liquid mass ratio of the deep eutectic solvent to the enzyme pretreated plant straw powder is 100:(1-30); and / or, The reaction temperature of the dissociation-in-situ esterification reaction is 40° C. to 170° C.; and / or, The reaction time of the dissociation-in-situ esterification reaction is 0.5 to 6 hours; and / or, After the dissociation-in-situ esterification reaction is completed, ethanol or acetone is added to the reaction solution, and the in-situ esterified holocellulose solid and filtrate I are obtained by suction filtration. After the ethanol or acetone is separated from the filtrate I, water is added and the lignin solid and filtrate II are obtained by suction filtration. After the water is separated from the filtrate II, a deep eutectic solvent that can be reused is obtained.

8. The preparation method according to claim 1, characterized in that: In step (4), the oxidant is one or more of ozone, potassium permanganate, hydrogen peroxide, sodium persulfate, ammonium persulfate, sodium chlorite, and sodium hypochlorite.

9. The preparation method according to claim 1, characterized in that: In step (4), The solid-liquid mass ratio of the deionized water, the in-situ esterified holocellulose, and the oxidant is 100:(3-30):(1-15); and / or, The pH value of the mixed solution is 2 to 12; and / or, The reaction temperature of the oxidation reaction is 30°C to 90°C; and / or, The reaction time of the oxidation reaction is 0.5h to 6h.

10. The preparation method according to claim 1, characterized in that: In step (5), The solid-liquid mass ratio of the deionized water and the in-situ esterified holocellulose in the dispersion is 100:(0.1-30); and / or, The mechanical treatment is ultrasonic treatment, wherein the ultrasonic frequency of the ultrasonic treatment is 5 to 100 kHz, the power range is 50 to 700 W, and the treatment time is 1 to 90 min; and / or, The mechanical treatment is ball milling, the rotation speed of the ball milling is 50 to 1100 rpm / min, and the treatment time is 1 to 90 min; and / or, The mechanical treatment is a high-speed dispersion treatment, the rotation speed of the high-speed dispersion treatment is 1000-100000 rpm / min, and the treatment time is 1-90 min; and / or, The mechanical treatment is a high-pressure homogenization treatment, the treatment pressure of the high-pressure homogenization treatment is 500-3000 bar, the treatment flow rate is 10-2000 mL / h, and the treatment time is 1-90 min.

Citation Information

Patent Citations

  • Dissolution and processing of cellulose using ionic liquids

    CN101007853A

  • Method for preparing mlcrocrystalline cellulose by corps straw

    CN101503865A

  • Acidic deep-eutectic solvent, preparation thereof and application of acidic deep-eutectic solvent in pretreatment of straws and improvement of enzymolysis efficiency

    CN112899313A

  • Lignocellulosic bioplastics and composites, and methods of forming and using same

    CN116457528A

  • Graphite fluoride-nanocellulose two-dimensional interwoven layered material as well as preparation method and application thereof

    CN117511624A

Cited By

  • Mild and environment-friendly straw-based cellulose nanofibril and preparation method thereof

    CN121428684A